Employing Photocatalysis for the Design and Preparation of DNA‐Encoded Libraries: A Case Study. Issue 4 (11th February 2021) - Kölmel, Dominik K.; Zhu, Hongyao; Flanagan, Mark E.; Sakata, Sylvie K.; Harris, Anthony R.; Wan, Jinqiao; Morgan, Barry A.
Abstract: This Personal Account describes the authors' foray into DNA‐encoded libraries. The article addresses several key aspects of this hit generation technology, from the development of new synthetic methodology to the subsequent conception, design, and delivery of a DNA‐encoded library. In particular, we have been engaged in adapting photocatalytic reactions to the idiosyncratic requirements of DNA‐encoded chemistry. We have chosen one such methodology, namely a photocatalytic [2+2] cycloaddition reaction, to showcase how we employed property‐based computational analyses to guide the selection and validation of building blocks for the production of a library. Ultimately, these novel bond disconnections and design principles led to the assembly of a DNA‐encoded library that is composed of structurally diverse compounds within largely desirable property space and, therefore, well positioned to deliver novel chemical matter for drug discovery programs. Abstract : This Personal Account summarizes our recent efforts to adapt new photocatalytic transformations for the synthesis of DNA‐encoded libraries. Specifically, our approach to this hit identification platform is exemplified by delineating how we conceived, designed, and prepared a DNA‐encoded library that is based on a photocatalytic [2+2] cycloaddition reaction as the key step.